INTEGRATING CHARACTER EDUCATION INTO ENTREPRENEURSHIP EDUCATION PROGRAMS: HOLISTIC - Wulan Vinara; Alfin Syaiful Herdiana; Ichsan Fauzi Rachman (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
The article discusses the importance of integrating character education into entrepreneurship education. Character education is highlighted as an important factor in increasing access to knowledge, encouraging community participation, encouraging entrepreneurship and innovation, and developing skills. The method used in writing this article is literature review. This type of research involves the analysis and synthesis of various sources relevant to the topic under study. The systematic and structured nature of the literature review methodology enables evaluation of the quality of sources, identification of research gaps, development of theoretical frameworks, and improvement of research quality. The results of the literature review can thus become a reference for new literature. In addition, Character Education is not only interpreted as something that must be done but becomes an attitude and ability of a person in. This research emphasizes the importance of character in supporting entrepreneurship education, suggesting strategies such as expanding access to technology, integrating character education into entrepreneurship education in higher education, applying character education to the younger generation, empowering women and vulnerable groups, creating an entrepreneurial spirit with character, supporting SMEs, and raising awareness through campaigns.